Time Trends in Colorectal Cancer Incidence From 1992 to 2016 and Colorectal Cancer Mortality From 1980 to 2018 by Age Group and Geography in Canada. (11th February 2023) - Decker, Kathleen M.; Lambert, Pascal; Bravo, Jen; Demers, Alain; Singh, Harminder
Abstract : INTRODUCTION: Several reports have highlighted increasing colorectal cancer (CRC) incidence among younger individuals. However, little is known about variations in CRC incidence or mortality across age subgroups in different geographical locations. We aimed to examine time trends in CRC incidence and mortality in Canada by age group and geography in this population-based, retrospective cohort study. METHODS: Individuals diagnosed with CRC from 1992 to 2016 or who died of CRC from 1980 to 2018 in Canada were studied. Geography was determined using an individual's postal code at diagnosis from the Canadian Cancer Registry or province or territory of death from the Canadian Vital Statistics Death Database. Geography was categorized into Atlantic, Central, Prairies, West, and Territories. Canadian Cancer Registry data were used to determine CRC incidence from 1992 to 2016. Canadian Vital Statistics Death data were used to determine CRC mortality from 1980 to 2018. RESULTS: Among all age groups, CRC incidence was highest in Atlantic Canada, was lowest in Western Canada, and increased with age. CRC incidence increased over time for individuals aged 20–44 years and was stable or decreased for other age groups in all regions. CRC mortality was highest in Atlantic Canada and lowest in the Prairies and Western Canada. CRC mortality decreased for individuals in all age groups and regions except among individuals aged 20–49 years in the Territories. DISCUSSION: Most of Canada has not yet seen an increase in CRC burden in the age group of 45–49 years, which is a reason to not lower the start age for CRC screening in Canada. Targeted CRC screening should be considered for individuals younger than 50 years who live in the Territories.